The Epistemic Virtues of a Closed Mind: Effective Science Reporting in the Golden Age of the Con - Bishop, Michael A.; Trout, J. D. (Frontiers in Communication, 2021)
A financial confidence game (or “con”) aims to separate you from your money. An epistemic con aims to influence social policy by recruiting you to spread doubt and falsehood about well-established claims. You can’t be conned if you close your wallet to financial cons and your mind to epistemic cons. Easier said than done. The epistemic con has two elements. First are magic bullet arguments, which purport to identify the crucial fact that proves some well-established hypothesis is false. Second are appeals to epistemic virtue: You should be fair, consider the evidence, think for yourself. The appeal to epistemic virtue opens your mind to the con; countless magic bullet arguments keep it open. As in most cons, you (the mark or victim) don’t understand the game. You think it’s to find the truth. But really, it’s to see how long the con artist can string you along as his unwitting shill (an accomplice who entices victims to the con). Strategic Reliabilism says that reasoning is rational to the extent it’s accurate, easy to use, and practical (it applies to significant problems). It recommends that we give close-minded deference to settled science, and thus avoid a large class of epistemic cons. Settled science consists of the general consensus of scientific experts. These experts are defined not by their personal characteristics but by their roles within the institutions of science. Close-minded deference is not blind faith or certainty. It is belief that does not waver in the face of objections from other (less reliable) sources. When the epistemic con is on, the journalist faces a dilemma. Report on magic bullet arguments and thereby open people’s minds to the con. Or don’t, and feed the con artist’s narrative that evidence is being suppressed. As always, the journalist’s best response is sunshine: Report on the story of the epistemic con. Show people how they work. The story of the epistemic con has, at its heart, a wicked reveal: Your reaction to the story is itself part of the story, and it tells you whether the true villain of the story lurks within you.